Digital Extension Interactive Voice Response (IVR) mLearning: Lessons Learnt From Uganda Pig Value Chain - Dione, Michel; Kangethe, Edwin; Poole, Elizabeth Jane; Ndiwa, Nicholas; Ouma, Emily; Dror, Iddo (Frontiers in Veterinary Science, 2021)
We implemented a pilot randomized controlled trial (RCT) with 408 smallholder pig farmers to assess the effectiveness of Interactive Voice Response (IVR) in delivering biosecurity messages for the control of African swine fever (ASF) in Uganda. Our results show that IVR significantly improved knowledge of farmers who had never been exposed to training on biosecurity before. Furthermore, it enhanced knowledge for farmers who had received face to face (f2f) training in biosecurity in addition to IVR. This group of farmers recorded the highest knowledge gain compared to other groups. IVR technology was perceived by farmers as a new technology capable of transforming their lives because it is time efficient and has high potential for resource saving and flexibility. IVR also seems to be more gender sensitive compared to f2f training as it addresses some of the constraint’s women face in accessing conventional extension services. If documented technical challenges are addressed, IVR could be an innovative way to deliver important advisory information, such as biosecurity messages, to farmers. The scalability of IVR could further be explored and its feasibility assessed for wider use by the extension systems in Uganda and elsewhere.